Assessment of acetylcholinesterase (AChE) from Oreochromis mossambicus (Cuvier, 1831) as a source of enzyme for insecticides detection - Muhammad, Umar Abubakar; Tham, Lik Gin; Perumal, Natarajan; Mohd Daud, Hassan; Yasid, Nur Adeela; Abd. Shukor, Mohd. Yunus (Hibiscus Publisher, 2016)
In this work we assess the potential of acetylcholinesterase (AChE) from Oreochromis mossambicus (Toman) as a sensitive test for the presence of insecticides. The partial purification and characterization of a soluble AChE from Oreochromis mossambicus brain tissues using affinity chromatography gel (procainamide–Sephacryl S-1000) showed that the partially purified AChE was most active on acetylthiocholine (ATC) but had low activities on propionylthiocholine (PTC) and butyrylthiocholine (BTC), indicating that the partially purified fraction was predominantly AChE. Soluble AChE was partially purified 9.27-fold with a 91.12% yield. The partially purified AChE displayed the highest activity on ATC at pH 7 and at 30oC using 0.1 M Tris buffer. The enzyme exhibited Michaelis-Menten kinetic constants, Km, for ATC, BTC and PTC at 36, 77 and 250 µM, respectively, and the maximum velocities, Vmax, were 18.75, 0.12 and 0.05 µmol/min/mg protein, respectively. Moreover, the AChE from Oreochromis mossambicus presented comparable sensitivity to carbamates and organophosphates insecticides than that from Electrophorus electricus and many other fish AChE by comparing half maximal inhibitory concentration values. Therefore, the enzyme is a valuable source for insecticides detection in Malaysian waters at lower cost.